This Pengaruh layanan penguasaan konten teknik assertive training format klasikal terhadap peningkatan perilaku asertif siswa kelas VIII SMP Negeri 30 Bengkulu selatan: enguasaan Konten, Perilaku Asertif, Teknik Assertive Training - Yolanda Suci Rahmadani yolanda; I Wayan Dharmayana; Arsyadhani Mishbahuddin (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2023)
This research was motivated by the existence of low student assertive behavior at SMP Negeri 30 Bengkulu Selatan This study intends to describe how service content mastery of traditional assertive training methodologies affects students in the eighth grade at SMP Negeri 30 Bengkulu Selatan's increased assertive conduct. An experimental one-group pretest-posttest design method is employed in this study methodology. 101 pupils made up the study's population. 33 students made up the sample in this study. Through the use of random sampling, samples were collected. A questionnaire with a Likert scale was employed in this study's data collection method.. The data analyzed by the t test . The results indicate an increase in students' assertive behavioor. The average value before the services is provided is 84.2 in the low category, after being given the service, the average score became 117.3 in the high category. The results show the value of t = -37.984 (p=<0.05). This means that there is a significant influence of content mastery services in the classical format of assertive training techniques on increasing students' assertive behavior.